Expression of melanoma differentiation associated gene 5 is increased in human gastric mucosa infected with Helicobacter pylori. Issue 9 (29th March 2012) - Tatsuta, Tetsuya; Imaizumi, Tadaatsu; Shimoyama, Tadashi; Sawaya, Manabu; Kunikazu, Tanji; Matsumiya, Tomoh; Yoshida, Hidemi; Satoh, Kei; Fukuda, Shinsaku
Abstract : Helicobacter pylori infection is associated with gastroduodenal diseases. Melanoma differentiation associated gene 5 (MDA5) plays a role in antiviral host defense. We investigated the effect of H pylori infection on MDA5 expression in human gastric mucosa. Biopsy samples from the antrum and corpus were obtained from 33 patients. MDA5 mRNA and protein were examined by real-time PCR and immunohistochemical staining. Histological gastritis was graded according to updated Sydney System. MDA5 mRNA was significantly increased in the antrum infected with H pylori . MDA5 protein positively stained in infiltrating mononuclear cells. MDA5 mRNA expression was significantly correlated with the grade of glandular atrophy (rs = 0.767) and intestinal metaplasia (rs = 0.748) in the corpus with H pylori infection. These results indicate that MDA5 may be involved in innate immune reactions against H pylori and associate with glandular atrophy and intestinal metaplasia in patients with H pylori infection.